Optical characterization of the Central Nervous System of Haementeria officinalis - Díaz Torres, E; Vargas Sánchez, J; Lomelí Mejía, P A; Cruz Orea, A (Revista Mexicana de Ingenieria Biomedica, 2017)
The failure in the neuron regeneration in the central nervous system (CNS) in higher vertebrates, is a not completely solved problem, this limits the rehabilitation of many motor conducts after an injury in the spinal cord. In neuronal regeneration multiple factors are involved, between them those that induce the neurite outgrowth which has been studied to try to encourage the extension and reconnection of the injury neurons with their blanks. The regeneration of the CNS of leeches has been intensely studied because allows to approach the problem at different levels with different techniques. In this study the optical absorption spectrum of the CNS and the tissue of the leech H. officinalis was obtained, by using photoacoustic spectroscopy (PAS), in order to investigate the optimal wavelenghts for later irradiation of CNS cells and tissue of H. officinalis. The results of this study show that the CNS of these organisms absorbs in the region of 300 nm to 500 nm, and the tissue samples has a maximun of optical absorption near to 300 nm, besides were observed evident differences between the optical absorption spectra of CNS with injury and the control (without injury).